2018
DOI: 10.18857/jkpt.2018.30.6.211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transcranial Direct Current Stimulation on Lower Limb Muscle Activation and Balance Ability in Soccer Player

Abstract: This study is to investigate influence of tDCS on lower limb muscle activity and balance ability in soccer player. Methods: Sessions were conducted with 15 subjects in tDCS group and 15 in action observation training group for 20 minutes, 5 sessions a week, for 8 weeks. All soccer players underwent 30 minutes of plyometric training before main exercise. To evaluate lower limb muscle activation, rectus femoris and biceps femoris were taken measure using surface electromyogram system and to evaluate balance abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In the study of Kan et al, electrodes were placed in unilateral cerebral motor areas (right M1), while bilateral tDCS over M1 was used in this study. Recent studies have been reported that tDCS at bilateral brain motor areas could elevate muscle power in the lower limb ( Yang et al, 2018 ; Huang et al, 2019 ). Yang et al (2018) found that the group receiving 2 mA of stimulation for 20 min targeting the motor cortex bilaterally of tDCS with Halo Sport device was more effective in improving balance ability and muscle activation of the RF and BF than action observation training group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study of Kan et al, electrodes were placed in unilateral cerebral motor areas (right M1), while bilateral tDCS over M1 was used in this study. Recent studies have been reported that tDCS at bilateral brain motor areas could elevate muscle power in the lower limb ( Yang et al, 2018 ; Huang et al, 2019 ). Yang et al (2018) found that the group receiving 2 mA of stimulation for 20 min targeting the motor cortex bilaterally of tDCS with Halo Sport device was more effective in improving balance ability and muscle activation of the RF and BF than action observation training group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been reported that tDCS at bilateral brain motor areas could elevate muscle power in the lower limb ( Yang et al, 2018 ; Huang et al, 2019 ). Yang et al (2018) found that the group receiving 2 mA of stimulation for 20 min targeting the motor cortex bilaterally of tDCS with Halo Sport device was more effective in improving balance ability and muscle activation of the RF and BF than action observation training group. Huang et al (2019) also observed a performance benefit from the Halo Sport, specifically improving repeated sprint cycling power output.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations